Methionine synthesis and glycine betaine demethylation are intricately intertwined in cosmopolitan marine bacteria - Michaela A. Mausz; Andrew R. J. Murphy; Maria del Mar Aguilo-Ferretjans; Andrew Hitchcock; Mary Ann Moran; David J. Scanlan; Yin Chen; Ian D. E. A. Lidbury (Proceedings of the National Academy of Sciences, 2025)
Across all domains of life, cobalamin-dependent methyltransferases have diversified to perform a range of crucial functions, such as methionine synthesis and the demethylation of various reduced nitrogen and sulfur compounds. These large modular enzymes typically possess three substrate-binding domains, two binding either the methyl donor or methyl acceptor, as well as a cobalamin-binding domain. Here, by challenging the current paradigm of glycine betaine (GBT) catabolism, we have identified a unique methyltransferase in aerobic environmental bacteria that has a dual function both as a methionine synthase and a GBT methyltransferase. Using the marine bacterium Ruegeria pomeroyi DSS-3 as a model, we demonstrate that a core cobalamin-binding domain (MtgC) and a bidirectional methyltransferase (MtgD) are essential for both methionine synthesis and GBT demethylation. MtgC is phylogenetically distinct from the cobalamin-binding domains of either the classical methionine synthase (MetH) or the GBT methyltransferases found in anaerobic bacteria and archaea. Across the global ocean, mtgC expression is frequently greater than previously known GBT catabolic pathways due to its occurrence in abundant cosmopolitan marine bacteria. Thus, we uncover a unique relationship between GBT catabolism and methionine synthesis in nature and identify a major route for N-osmolyte demethylation in the global ocean.